Preoperative planning of femoral head reduction osteotomy using 3D printing model: A report of two cases - Önder Kalenderer; Serkan Erkuş; Ali Turgut; İrem Hazal İnan (Acta Orthopaedica et Traumatologica Turcica, 2019)
The deformed and enlarged femoral head secondary to hip diseases such as Legg Calve Perthes and Developmental Dysplasia usually causes impingement between the aspherical head and the acetabulum. To restore and reduce the size of enlarged femoral head, a femoral head reduction technique has been described previously. The goal is to obtain a spherical femoral head and to cover the gliding surface with best available cartilage. Planning of osteotomy to achieve spherical head is the crucial point of surgery. It is usually done intra-operatively and dependent on experience of surgeon. Preoperative 3- Dimension (D) modeling of femoral head is commonly preferred to minimize this risk. In this technical note, preoperative planning with 3-D printing was demonstrated in two separate patients with Legg-Calve-Perthes Disease and developmental hip dysplasia. Surgical time was approximately 150 and 120 min, respectively. Blood loss was 230 and 300 cc, respectively. Patients were followed up 9 months and 12 months, respectively. None of the patients in this study developed avascular necrosis; however, the follow-up period is very limited. Moreover, none of the patients developed post-operative complications or required additional surgery. With a more detailed preoperative planning done on computer model and printed in 3-D, one can mimic the surgical procedure before the procedure. Finally, this technique is advantageous both for the patient and surgeon. Keywords: Deformation, Femoral head, Preoperative planning, Hip, Three dimensional printing